2001
DOI: 10.1159/000050023
|View full text |Cite
|
Sign up to set email alerts
|

Mice Genetic Immunization with Plasmid DNA Encoding a Secreted Form of HSV-1 gB Induces a Protective Immune Response against Herpes simplex Virus Type 1 Infection

Abstract: Intramuscularly (i.m.) delivered plasmid DNA encoding a secreted form of glycoprotein B of herpes simplex virus type 1 (HSV-1 gB1s) was evaluated for the ability to elicit a protective immune response in Balb/c mice. Animals received three i.m. injections of a gB1s expression plasmid (pRP-RSV-gB1s) or of a wild-type transmembrane gB1 coding plasmid (pRP-RSV-gB1), while control mice were injected with the vector alone (pRP-RSV). A specific antibody response was observed in almost all immunized animals, and in m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 17 publications
1
10
0
Order By: Relevance
“…1,6,7 Virus-specific CTLs have been induced by pDNA vaccine carrying antigens for influenza virus, 19,20 lymphocytic choriomeningitis virus, 21,22 human immunodeficiency virus-1, 23 and hepatitis B 24 and C 25 viruses. When a pDNA vaccine encoding an HSV glycoprotein is immunized into Balb/c 8,[26][27][28][29][30][31][32][33] or Hartley guinea pig 12,34 via the intramuscular route, humoral responses (Th2 and antibody) are predominantly elicited. The CTL response is induced when a Th1 cytokine 35 or the granulocyte-macrophage colony stimulating factor (GM-CSF) 6 is employed as an adjuvant in combination with the pDNA vaccine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,6,7 Virus-specific CTLs have been induced by pDNA vaccine carrying antigens for influenza virus, 19,20 lymphocytic choriomeningitis virus, 21,22 human immunodeficiency virus-1, 23 and hepatitis B 24 and C 25 viruses. When a pDNA vaccine encoding an HSV glycoprotein is immunized into Balb/c 8,[26][27][28][29][30][31][32][33] or Hartley guinea pig 12,34 via the intramuscular route, humoral responses (Th2 and antibody) are predominantly elicited. The CTL response is induced when a Th1 cytokine 35 or the granulocyte-macrophage colony stimulating factor (GM-CSF) 6 is employed as an adjuvant in combination with the pDNA vaccine.…”
Section: Discussionmentioning
confidence: 99%
“…Live or attenuated HSV vaccine is capable of inducing both antibody and CTL responses. 7 Although humoral responses induced by intramuscular pDNA vaccine protocols protect animals from acute HSV infection, 8,[26][27][28][29][30][31] effectiveness of these strategies in controlling latent and recurrent infection has not been elucidated. The cellular immune responses may play important roles in antivirus defense, in case genetic vaccine will be applied to humans.…”
Section: Discussionmentioning
confidence: 99%
“…Although such adaptive transfer experiments have not been performed in previous studies on HSV genetic vaccines, cumulative evidence has demonstrated that protection against lethal HSV infection was successfully achieved by intramuscular pDNA vaccines that were capable of inducing humoral response but not CTLs. 1,[3][4][5]7,8 The data shown in Figure 7, however, do not indicate that CTLs did not play any role in antivirus defense, although it was shown that adaptive transfer of cell components failed to achieve viral clearance per se. Using gene knockout mice, Nass et al analyzed contribution of B cells, CD4 + and CD8 + T cells to the anti-HSV protection, clearly showing that all the populations are essential for the effective prophylactic immunity in their vaccine strategy.…”
Section: Discussionmentioning
confidence: 98%
“…3,4,7,8 In our previous report, 5 mg of gB pDNA administered via an intravascular route allowed approximately 80% of mice to survive fatal HSV infection. 13 The present findings indicate that the coadministration of the IL-12 expression construct further reduced the dose of the vaccine that is required for induction of successful immune prevention.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation